Does the Status of Governance Practices Differentiate Countries in the Forex Market? - Ahamed, Naseem (Indian Journal of Finance, 2014)
Liberalization of the Indian economy (in 1991) and many other economies contemporarily made the survival of isolated economies out of question. With the opening up of economic barriers, better governance practices flowed from good governed to relatively badly governed countries. Now, with increased industrialization and opening up of economies for trade and commerce, political boundaries of nations have been transgressed by businesses. However, this opportunity of making money abroad may also bring some inconvenience to the parent company as it might suffer losses or receive eroded profits when the foreign currency is converted to the local currency at prevailing rates (Pandey, 2010). There may be several other examples like this in real and hypothetical scenarios, and these need to be addressed with prudence. This topic does the same as it calls for attention towards these risks and precautions/remedies available for the same. Apart from the MNCs, there are people who enter into the currency markets for speculative gains. These traders do not require these foreign currencies, but they buy/sell them for making profits from the existing market situations. The proportion of these traders is much larger than those who need foreign currency to make payments, give wages, and so forth. The present paper intends to provide an econometric model for the traders in the currency market which could, up to a reasonable extent, anticipate the fluctuations in major globally transacted currency pairs. This would be handy for the traders and for large businesses running overseas (which have to deal in different currency regions) as they can accordingly decide whether to invest in a particular currency or not.